MiD51 Is Important for Maintaining Mitochondrial Health in Pancreatic Islet and MIN6 Cells - Schultz, Julia; Warkus, Jeanette; Wolke, Carmen; Waterstradt, Rica; Baltrusch, Simone (Frontiers in Endocrinology, 2020)
Background: Mitochondrial dynamics are important for glucose-stimulated insulin secretion in pancreatic beta cells. The mitochondrial elongation factor MiD51 has been proposed to act as an anchor that recruits Drp1 from the cytosol to the outer mitochondrial membrane. Whether MiD51 promotes mitochondrial fusion by inactivation of Drp1 is a controversial issue. Since both the underlying mechanism and the effects on mitochondrial function remain unknown, this study was conducted to investigate the role of MiD51 in beta cells. Methods: Overexpression and downregulation of MiD51 in mouse insulinoma 6 (MIN6) and mouse islet cells was achieved using the pcDNA expression vector and specific siRNA, respectively. Expression of genes regulating mitochondrial dynamics and autophagy was analyzed by quantitative Real-Time PCR, glucose-stimulated insulin secretion by ELISA, and cellular oxygen consumption rate by optode sensor technology. Mitochondrial membrane potential and morphology were visualized after TMRE and MitoTracker Green staining, respectively. Immunofluorescence analyses were examined by confocal microscopy. Results: MiD51 is expressed in insulin-positive mouse and human pancreatic islet and MIN6 cells. Overexpression of MiD51 resulted in mitochondrial fragmentation and cluster formation in MIN6 cells. Mitochondrial membrane potential, glucose-induced oxygen consumption rate and glucose-stimulated insulin secretion were reduced in MIN6 cells with high MiD51 expression. LC3 expression remained unchanged. Downregulation of MiD51 resulted in inhomogeneity of the mitochondrial network in MIN6 cells with hyperelongated and fragmented mitochondria. Mitochondrial membrane potential, maximal and glucose-induced oxygen consumption rate and insulin secretion were diminished in MIN6 cells with low MiD51 expression. Furthermore, reduced Mfn2 and Parkin expression was observed. Based on MiD51 overexpression and downregulation, changes in the mitochondrial network structure similar to those in MIN6 cells were also observed in mouse islet cells. Conclusion: We have demonstrated that MiD51 plays a pivotal role in regulating mitochondrial function and hence insulin secretion in MIN6 cells. We propose that this anchor protein of Drp1 is important to maintain a homogeneous mitochondrial network and to avoid morphologies such as hyperelongation and clustering which are inaccessible for degradation by autophagy. Assuming that insulin granule degradation frequently suppresses autophagy in beta cells, MiD51 could be a key element maintaining mitochondrial health.